Criminal law-based copyright protection with entrepreneurial spirit - Wang, Wenjing (Frontiers in Psychology, 2022)
The aim is to optimize the enterprise criminal law-based copyright protection. This exploration discusses the role of the Entrepreneurial Spirit (ES) in criminal law-based copyright protection. In order to study the relationship between ES and criminal law-based copyright protection, the concepts of ES, criminal law-based copyright protection, and enterprise innovation are given. Next, by collecting literature, hypotheses are put forward. They include the relationship between ES and enterprise innovation, ES and the criminal law-based copyright protection, and the intermediary role of ES in the criminal law-based copyright protection and economic growth. Then, relevant models are established. Finally, the hypotheses are tested through experiments and empirical analysis, and the model is regressed to test the experimental data's robustness and the scale's reliability and validity. The empirical analysis shows that: (1) the significance of ES under the 1% index is greater than 0. It indicates that the higher managers' ES is, the greater the enterprise innovation is. (2) The significance of criminal law-based copyright protection on ES under the 1% index is greater than 0, and the regression coefficient is 0.59. This shows that criminal law-based copyright protection has a significant positive impact on ES. (3) Under the l% index, the significance of ES on economic growth is greater than 0, and the regression coefficient is 0.63. It shows that ES mediates the relationship between criminal law-based copyright protection and economic growth. Therefore, strengthening criminal law-based copyright protection improves the ES and leads to faster enterprise and regional economic development. Therefore, the state should pay attention to criminal law-based copyright protection to encourage innovation to promote enterprise development. This exploration studies the relationship between ES, economic growth, enterprise innovation, and criminal law-based copyright protection. The finding provides a theoretical reference for criminal law-based copyright protection.